How far actually is the Galactic Center IRS 13E3 from Sagittarius A*?. (26th March 2020) - Tsuboi, Masato; Kitamura, Yoshimi; Tsutsumi, Takahiro; Miyawaki, Ryosuke; Miyoshi, Makoto; Miyazaki, Atsushi
Abstract: The Galactic Center IRS 13E cluster is a very intriguing infrared object located at 0.13 pc from Sagittarius A^* (Sgr A^* ) in projection distance. There are arguments both for and against the hypothesis that a dark mass like an intermediate mass black hole (IMBH) exists in the cluster. We recently detected the rotating ionized gas ring around IRS 13E3, which belongs to the cluster, in the H30α recombination line using ALMA. The enclosed mass is derived to be M_encl.2× 10^4 M_, which agrees with an IMBH and is barely less than the astrometric upper limit mass of an IMBH around Sgr A^* . Because the limit mass depends on the true three-dimensional (3D) distance from Sgr A^*, it is very important to determine it observationally. However, the 3D distance is indefinite because it is hard to determine the line-of-sight (LOS) distance by usual methods. We attempt here to estimate the LOS distance from spectroscopic information. The CH_3 OH molecule is easily destroyed by the cosmic rays around Sgr A^* . However, we detected a highly excited CH_3 OH emission line in the ionized gas stream associated with IRS 13E3. This indicates that IRS 13E3 is located at r0.4 pc from Sgr A^* .